IMPLEMENTASI METODE PEMBELAJARAN TWO STAY TWO STRAY UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR TEKNOLOGI DASAR OTOMOTIF SISWA KELAS X TKRB SMKN 1 SEDAYU - Febryan Edwin Nur Ramadhan; Wardan Suyanto (Jurnal Pendidikan Vokasi Otomotif, 2019)
This study was intended to improve the activeness of the students and the learning outcomes on Basic Technology of Automotive course in SMK N 1 Sedayu through the implementation of two stay two stray method. This type of research is classroom action research (CAR) and was conducted in two cycles. The research design in each cycle uses four steps/stages of CAR as follows, (1) planning, (2) acting, (3) observing, and (4) reflecting. The research subjects are students of class X TKR B SMK N 1 Sedayu in even semester 2018/2019. Data collection process was conducted through the observation sheet to know how high the level of activeness of the students, and observe the implementation of two stay two stray method, and the evaluation test to know the level of student learning outcomes. The implementation of two stay two stray method successfully improves the activeness and the learning outcomes if the percentage of students activeness reaches 70% (good category) and as many as 75% of students have completed KKM (good category) namely the minimun score of learning outcomes is 75. The result of the research points out that the implementation of two stay two stray method in the learning process could improve the activeness of the students and the learning outcomes of grade X students of TKR B in SMK N 1 Sedayu. This is proven in cycle II the percentage of students activeness and learning outcomes have been reached the success indicator determined with the percentage of activeness reaches 76% (good category) and students completed KKM reaches 81% (very good category).